Concentration and velocity profiles in a polymeric lithium-ion battery electrolyte - Steinrück, Hans-Georg; Takacs, Christopher J.; Kim, Hong-Keun; Mackanic, David G.; Holladay, Benjamin; Cao, Chuntian; Narayanan, Suresh; Dufresne, Eric M.; Chushkin, Yuriy; Ruta, Beatrice; Zontone, Federico; Will, Johannes; et al. (Energy & Environmental Science)
Direct measurements of concentration and velocity profiles in a polymeric lithium-ion battery electrolyte provide insights into the transference number.

Interface between Water–Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans-Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir)

Tortuosity Effects in Lithium-Metal Host Anodes - Chen, Hao; Pei, Allen; Wan, Jiayu; Lin, Dingchang; Vilá, Rafael; Wang, Hongxia; Mackanic, David; Steinrück, Hans-Georg; Huang, William; Li, Yuzhang; Yang, Ankun; Xie, Jin; et al. (Joule)

Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Selbstbau eines digitalen Low-Cost-Fotometers für den Chemieunterricht - Witte, Thomas; Hanemann, Stefan; Sommerfeld, Herbert; Temmen, Katrin; Fechner, Sabine (CHEMKON)

Modeling and Simulation of an Industrial Formaldehyde Absorption System - Braz, Catarina G.; Lutters, Nicole; Rocha, Jorge; Alvim, Ricardo; Kenig, Eugeny; Matos, Henrique A. (Industrial & Engineering Chemistry Research)

Kinetics of Carbon Dioxide Removal Using N-Acetylglucosamine - Patil, Mayurkumar P.; Vaidya, Prakash D.; Kenig, Eugeny (ACS Omega)

Theoretical limits on the heat regeneration degree - Kronberg, Alexander; Glushenkov, Maxim; Knoke, Torben; Kenig, Eugeny (International Journal of Heat and Mass Transfer)

Numerical investigation of liquid flow morphology in structured packings - Olenberg, Alexander; Kenig, Eugeny (Chemical Engineering Science)

Numerical investigation of conjugate heat transfer in a pillow-plate heat exchanger - Zibart, A.; Kenig, E.Y. (International Journal of Heat and Mass Transfer)

Regeln der Kunst: Habitus, Literatur und ästhetische Form. - Eke, Norbert (Religiöse Erfahrung – Literarischer Habitus.)

Erstellung eines CFD-Modells für die Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius
Keywords: CFD; landwirtschaftliche Abfälle; Volume-of-Fluid

Utopie als/der Störung. Heiner Müller und die „Lücke im Ablauf“. - Eke, Norbert (Rhetorik. Ein Internationales Jahrbuch)

Wider die Literaturwerkstättenliteratur? – Der Autor als „Obertonsänger“. Clemens J. Setz und die Gegenwartsliteratur. - Eke, Norbert („Es gibt Dinge, die es nicht gibt“. Vom Erzählen des Unwirklichen im Werk von Clemens J. Setz.)

Phase Transformation Characterization by Means of High Temperature Digital Image Correlation for Graded Thermo-Mechanical Processing of Sheet Parts - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (The Minerals, Metals & Materials Series)

„Das Schöne ist das Durchsichtige“. Norbert Otto Eke und Christof Hamann im Gespräch mit Herta Müller. In: Herta Müller. - Eke, Norbert (Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann)

„Ein paar Freunde lachen. so verrückt daß ganz nahe / schon im Schach das Schweigen steht“. Lachen in Herta Müllers Texten. - Eke, Norbert (Herta Müller. Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann.)

Auswahlbibliographie (Herta Müller) - Eke, Norbert (Herta Müller. Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann.)

Popularisierung der Form. Volkstümlichkeit als Medium im Vormärz. In: Medien öffentlicher Rede nach Heine: zwischen Popularität und Populismus. Hg. von Dorothea Walzer. - Eke, Norbert (Beihefte zur Zeitschrift für deutsche Philologie)

Pilpul, oder: Er hatte geglaubt, es sei alles gut. Jüdische Mystik in Die Tochter. - Eke, Norbert (Im Kopf von Maxim Biller. Essays zum Werk.)